2017
DOI: 10.1177/2396987317746003
|View full text |Cite
|
Sign up to set email alerts
|

Minor stroke due to large artery occlusion. When is intravenous thrombolysis not enough? Results from the SITS International Stroke Thrombolysis Register

Abstract: on behalf of SITS InvestigatorsAbstract Purpose: Beyond intravenous thrombolysis, evidence is lacking on acute treatment of minor stroke caused by large artery occlusion. To identify candidates for additional endovascular therapy, we aimed to determine the frequency of non-haemorrhagic early neurological deterioration in patients with intravenous thrombolysis-treated minor stroke caused by occlusion of large proximal and distal cerebral arteries. Secondary aims were to establish risk factors for non-haemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 40 publications
9
65
1
1
Order By: Relevance
“…To prove the association of BPV and END, we adopted a definition of END as a ≥1‐point increase in NIHSS score during the first 72 hours after admission. And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies . And also, our findings were similar to that in the Chungs' study .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To prove the association of BPV and END, we adopted a definition of END as a ≥1‐point increase in NIHSS score during the first 72 hours after admission. And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies . And also, our findings were similar to that in the Chungs' study .…”
Section: Discussionsupporting
confidence: 92%
“…And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies. [4][5][6][7][8][9][10] And also, our findings were similar to that in the Chungs' study. 16 Both studies suggested that the acute in-hospital BPV was strongly associated with the risk of having a END.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, during the study period, anatomic data on the location of arterial occlusion was not recorded in SITS, contrary to more recent years. 21 Still, during the study period, IVT was a well-established therapy, and acute diagnostic TCD was implemented across a wide range of hospitals in Europe and beyond. A further limitation of our data set, the lack of specific time points for the performance of CTA or MRA, precludes us from comparing logistics and outcomes in patients undergoing TCD versus CTA/MRA.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The reason for excluding minor stroke from IV rt-PA trails might be that thrombolysis could increase the risk of ICH and the benefit of IV rt-PA within these patients is unclear so far. Several retrospective studies indicated that IV rt-PA was effective for acute minor stroke (Förster, 2011;Laurencin et al, 2015;Mazya, 2017;Meyer, Lavados, & Olavarria, 2016;Mittal, Rymer, & Lai, 2011), but lack of evidence from well-designed randomized controlled trials (RCTs). Several retrospective studies indicated that IV rt-PA was effective for acute minor stroke (Förster, 2011;Laurencin et al, 2015;Mazya, 2017;Meyer, Lavados, & Olavarria, 2016;Mittal, Rymer, & Lai, 2011), but lack of evidence from well-designed randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%